Aboveground biomass and its biotic and abiotic modulators of a main food bamboo of the giant panda in a subalpine spruce–fir forest in southwestern China. (19th June 2021) - Xiong, Xinyu; Zhu, Jiangling; Li, Sheng; Fan, Fan; Cai, Qiong; Ma, Suhui; Su, Haojie; Ji, Chengjun; Tang, Zhiyao; Fang, Jingyun
Abstract: As one of the main food bamboo species of the giant panda ( Ailuropoda melanoleuca ), Fargesia denudata is widely distributed in the understory of spruce–fir forests in the mountainous area of southwestern China. However, the driving factors of its biomass and distribution in the forests are still unclear. We conducted a systematic investigation of the tree and shrub layers (including bamboos) of 209 subplots (20 m × 20 m) in a Forest Global Earth Observatory plot, the Wanglang Plot (25.2 ha), to explore the effects of abiotic (topographic and soil characteristics) and biotic (tree density, total basal area (TBA), shrub coverage, etc.) factors on the aboveground biomass of F. denudata (bamboo biomass hereafter). Bamboo biomass averaged 1.17 ton/ha, with a large variation from 0 to 4.88 ton/ha (95% confidence interval) among the 209 subplots. Bamboo biomass increased significantly with elevation, slope and mean diameter at breast height of trees, and decreased significantly with tree density, shrub coverage and soil pH. However, bamboo biomass was not significantly correlated with tree TBA, aspect, soil organic matter or total nitrogen content. The random forest model indicated that topographic factors and biotic factors had greater influences on the bamboo biomass than soil characteristics in general. Specifically, topographic factors mainly affected the bamboo biomass by changing tree density and soil characteristics. Our results can provide valuable guidance for the protection of giant pandas and the management of subalpine spruce–fir forests.